Residing in the city, living on the fringe of the forest: differentiated forest leisure activities, significant urban adjustments. Issue 1 (2nd January 2017) - Lepillé, Romain; Evrard, Barbara; Bussi, Michel; Féménias, Damien
ABSTRACT: This contribution deals with the spatial and social distribution of forest-fringe residents of the Rouen metropolis (France) and demonstrates how their forest-based leisure activities indicate and play a role in establishing their environment. A multi-scale approach contextualizes the study, explains the survey strategy used and shows how and to what degree these residents live between the city and forest. The sample is based on four very different residential forms reflecting different means of living in the city and reveal different ways of using nature, thus leading us to contemporary redefinitions of city–nature relations, which lie at the heart of the issues and mutations facing our urban condition.